2021
DOI: 10.21848/asr.200072
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diadochokinesis in Typically Developing Children and Adults

Abstract: Purpose: The purpose of this study was to examine the characteristics of the rate and perceptual judgment of diadochokinesis (DDK) in typically developing children and adults.Methods: Participants were typically developing children aged 2;6 to 9;11 and normal adults. For DDK tasks, they were asked to repeat [p*a], [t*a], [k*a], [p*at*a], and [p*at*ak*a] accurately and quickly with one breath. The number of repetitions per second was measured as DDK rate for each stimuli. The perceptual judgment of DDK were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Several studies on neurotypical adults have shown that SMR tasks are produced faster than AMR tasks (e.g. Jang et al, 2020;Mousavi et al, 2020) . However, a screening of the results summarized in the review paper by Kent, Kim & Chen (2021) seems to indicate that such pattern is not present at all ages.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on neurotypical adults have shown that SMR tasks are produced faster than AMR tasks (e.g. Jang et al, 2020;Mousavi et al, 2020) . However, a screening of the results summarized in the review paper by Kent, Kim & Chen (2021) seems to indicate that such pattern is not present at all ages.…”
Section: Discussionmentioning
confidence: 99%
“…DDK performance is usually measured by means of the speech rate [ 2 ], calculated by either counting the number of repeated syllables within a previously fixed interval or by measuring the time needed to repeat a given sequence [ 3 ]. Performance in DDK tasks has been largely tested across different age groups (e.g., in children [ 4 , 5 , 6 , 7 , 8 ], in adolescents [ 4 , 6 , 7 , 9 ], in young adults [ 5 , 10 , 11 , 12 , 13 , 14 ] and in the elderly [ 10 , 12 , 15 , 16 ]), with the most prominent result showing a gradual increase in the DDK rates from childhood to middle adulthood, followed by decreased rates from late adulthood. Although most DDK studies have commonly centered their discussion on those changes in rate over time, less attention has been paid to the performance pattern arising from the comparison between SMR and AMR tasks across different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Although most DDK studies have commonly centered their discussion on those changes in rate over time, less attention has been paid to the performance pattern arising from the comparison between SMR and AMR tasks across different age groups. Additionally, many DDK studies on adults have surprisingly reported faster rates for SMR sequences relative to AMR syllables [ 5 , 12 , 13 , 14 , 17 , 18 ], which is a counterintuitive result since one would rather expect the repetition of a single syllable to reach faster rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations